2016
DOI: 10.1074/jbc.m115.700336
|View full text |Cite
|
Sign up to set email alerts
|

Glioma-associated Oncogene 2 Is Essential for Trophoblastic Fusion by Forming a Transcriptional Complex with Glial Cell Missing-a

Abstract: Cell-cell fusion of human villous trophoblasts, referred to as a process of syncytialization, acts as a prerequisite for the proper development and functional maintenance of the human placenta. Given the fact that the main components of the Hedgehog signaling pathway are expressed predominantly in the syncytial layer of human placental villi, in this study, we investigated the potential roles and underlying mechanisms of Hedgehog signaling in trophoblastic fusion. Activation of Hedgehog signaling by a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
(41 reference statements)
2
13
0
Order By: Relevance
“…Recently, we demonstrated the expression patterns of HH ligands and activity of the HH signaling pathway in both human and murine placentas, and further confirmed the versatile roles of HH signaling in placental development and functions including steroidogenesis, epithelialmesenchymal transition and syncytialization (2,(15)(16)(17). In the present study, we have revealed that activation of HH pathway promotes the conversion of active cortical to inactive cortisone through GLI2-mediated induction of 11␤-HSD2 expression in human tropoblasts.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Recently, we demonstrated the expression patterns of HH ligands and activity of the HH signaling pathway in both human and murine placentas, and further confirmed the versatile roles of HH signaling in placental development and functions including steroidogenesis, epithelialmesenchymal transition and syncytialization (2,(15)(16)(17). In the present study, we have revealed that activation of HH pathway promotes the conversion of active cortical to inactive cortisone through GLI2-mediated induction of 11␤-HSD2 expression in human tropoblasts.…”
supporting
confidence: 81%
“…As previously reported, 11␤-HSD2 expression is upregulated during the process of placental trophoblasts fusion, namely syncytialization, and HH/GLI2 is involved in directing syncytialization (15,21). To exclude the possibility that HH/GLI2-induced 11␤-HSD2 expression is resulted from the trophoblasts fusion, we knocked down GLI2 in human trophoblast-like choriocarcinoma JAR cells, which express 11␤-HSD2 but show a weak ability to fuse (22,23), and checked the 11␤-HSD2 mRNA and protein levels.…”
Section: Hh/gli2-induced 11␤-hsd2 Expression Is Independent Of Syncytsupporting
confidence: 68%
See 1 more Smart Citation
“…Immunofluorescence staining was performed as described previously. 49 The antibodies used were as follows: CCR3 (ab36827, Abcam), vimentin (sc26002, Santa Cruz Biotechnology), CC10 (sc365992, Santa Cruz Biotechnology), MUC5AC (ab3649, Abcam), SPDEF (ab197375, Abcam), FOXA2 (Santa Cruz Biotechnology), Alexa555 or Alexa488-conjugated secondary antibody (Invitrogen, Grand Island, NY). Semi-quantitative histomorphometry for PAS, immunohistochemistry and immunofluorescence staining was performed blindly in 10 different fields for each lung section by using Image-Pro Plus 6.0 software (Media Cybernetics, Silver Spring, MD) as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have indicated that Hh signaling was required for EMT process of human trophoblast cells, the pregnant maintenance, placental development [27,28,[51][52][53]. Thus, in the present study, we firstly investigated the expression of Shh signaling core members in health human placental villi, our results showed that the Shh/Ptch/Smo/Gli2/Gli3 signaling axis preferred to be activated in CTB layer, and Shh protein was decreased in villous tissue of recurrent miscarriage patients while compared to the healthy control.…”
Section: Discussionmentioning
confidence: 99%